Le coût de la mort dans les communautés chrétiennes en Éthiopie - Stéphane Ancel (Afriques)
In Orthodox Christian communities in Ethiopia, the loss of a person entails a considerable economic cost for the families concerned, due to funeral ceremonies and the number of attendees. Death is an occasion for transfers of material goods and exchanges of services between the family, community and church. Rather than merely calculating the cost of death for a family, this article focuses on the reasons for, and characteristics of, the exchanges triggered by a death in contemporary Christian Ethiopia. This study of the economics of death sheds light on a system of gifts and countergifts and on the deceased person’s and his/her family’s savings plans.